Hubungan Kepatuhan Minum Obat dengan Kejadian Cacat kusta di Puskesmas Batumarmar Pamekasan - Vadya Friska (Pusat riset dan Inovasi Nasional, 2025)
Morbus Hansen, or leprosy, is a chronic infectious disease caused by the bacterium Mycobacterium leprae. There are two types of leprosy, namely MB (Multi Bacillary) and PB (Pauci Bacillary). According to the WHO, the level of disability due to leprosy is divided into three levels: Level 0, Level 1, and Level 3. This study is an analytic observational study using a cross-sectional research design, involving 45 respondents selected through total sampling technique. Data collection was carried out by filling out a questionnaire consisting of questions regarding leprosy medication compliance. Data analysis used the chi-square test and prevalence rate. The results showed no association between medication compliance (p=0.092, PR=2.0) and the incidence of leprosy disability at the Batumarmar Health Center, Pamekasan Regency. The conclusion of this study indicates that although theoretically adherence to medication can lead to disability in leprosy patients, the results of this study show something different. The difference between the results of this study and the theory may be due to other factors affecting disability. The suggestion is that the health center is expected to improve the monitoring system to evaluate patient compliance with treatment. Support from medical personnel and families is also needed to encourage patients to be more consistent in undergoing therapy.